'You can't just put somebody in a situation with no armour'. An ethnographic exploration of the training and support needs of homecare workers caring for people living with dementia. (November 2021) - Leverton, Monica; Burton, Alexandra; Beresford-Dent, Jules; Rapaport, Penny; Manthorpe, Jill; Mansour, Hassan; Guerra Ceballos, Stefanny; Downs, Murna; Samus, Quincy; Dow, Briony; Lord, Kathryn; Cooper, Claudia
Background: Homecare workers carry out complex work with people living with dementia, while under-supported, undervalued and undertrained. In this ethnographic study, we explore the skills, training and support needs of homecare workers supporting people living with dementia. Research Design and Methods: We conducted 82 interviews with people living with dementia ( n = 11), family caregivers ( n = 22), homecare staff ( n = 30) and health and social care professionals ( n = 19) and conducted 100-hours of participant observations with homecare workers ( n = 16). We triangulated interview and observational findings and analysed data thematically. Results: We developed four themes: 1) 'Navigating the homecare identity and role': describing challenges of moving between different role identities and managing associated expectations, 2) 'Developing and utilising relational and emotional skills': boundaries between caring and getting emotionally involved felt blurred and difficult to manage, 3) 'Managing clients who resist care': homecare workers experienced clients' reactions as challenging and felt "thrown to the wolves" without sufficient training, and 4) 'Drawing on agency and team support': homecare work could be isolating, with no shared workplace, busy schedules and limited opportunity for peer support. Discussion and Implications: It is important that training and support for homecare workers addresses the relational, emotional and rights-based aspects of the role. Where a flexible, responsive, person-centred service is required, corresponding training and support is needed, alongside organisational practices, taking account of the broader context of the homecare sector.